A Helicopter lands on the camps ends of Camp Finney, Wapusk National Park - Bazely, Dawn (1982)
The helicopter pilot skillfully lands the bright orange bird on the camp ends' grounds at Camp Finney, Wapusk National Park. The camp is very green and some flowers can even be seen in the distance